American narratives of social and environmental crisis: Laura Restrepo's La novia oscura (1999) and Nancy Huston's Le Club des miracles relatifs (2016). Issue 3 (January 2018) - Averis, Kate
Abstract : This article explores the engagement with the degradation of the natural environment in Restrepo's La novia oscura (1999) [ The Dark Bride (2001)] and Huston's Le Club des miracles relatifs ['The Club of Relative Miracles'] (2016). It demonstrates the complex and interrelated nature of these American narratives of ecofiction, and by extension the necessarily transnational nature of the genre, which must also engage with a series of corresponding issues such as transnational capital and exploitation of labour, social inequality, gender violence, and the commodification of society. Employing a transnational ecofeminist theoretical approach, the article demonstrates the interrelated nature of social and environmental degradation in each novel through the combination of historical and literary discourses. It then considers the connection established in each novel between environmental degradation, hegemonic masculinity and violence towards women, before concluding with a discussion of the innovative literary style employed to drive home each author's urgent, unapologetic political message.